Inhibitory Effects of Varespladib, CP471474, and Their Potential Synergistic Activity on Bothrops asper and Crotalus durissus cumanensis Venoms - Sara Quiroz; Isabel C. Henao Castañeda; Johan Granados; Arley Camilo Patiño; Lina María Preciado; Jaime Andrés Pereañez (Molecules, 2022)
Snakebite is a neglected tropical disease that causes extensive mortality and morbidity in rural communities. Antivenim sera are the currently approved therapy for snake bites; however, they have some therapeutic limitations that have been extensively documented. Recently, small molecule toxin inhibitors have received significant attention as potential alternatives or co-adjuvant to immunoglobulin-based snakebite therapies. Thus, in this study, we evaluated the inhibitory effects of the phospholipase A2 inhibitor varespladib and the metalloproteinase inhibitor CP471474 and their synergistic effects on the lethal, edema-forming, hemorrhagic, and myotoxic activities of Bothrops asper and Crotalus durissus cumanensis venoms from Colombia. Except for the preincubation assay of the lethal activity with B. asper venom, the mixture showed the best inhibitory activity. Nevertheless, the mix did not display statistically significant differences to varespladib and CP471474 used separately in all assays. In preincubation assays, varespladib showed the best inhibitory activity against the lethal effect induced by B. asper venom. However, in independent injection assays, the mix of the compounds partially inhibited the lethal activity of both venoms (50%). In addition, in the assays to test the inhibition of edema-forming activity, the mixture exhibited the best inhibitory activity, followed by Varespladib, but without statistically significant differences (p > 0.05). The combination also decreased the myotoxic activity of evaluated venoms. In these assays, the mix showed statistical differences regarding CP471474 (p < 0.05). The mixture also abolished the hemorrhagic activity of B. asper venom in preincubation assays, with no statistical differences to CP471474. Finally, the mixture showed inhibition in studies with independent administration in a time-dependent manner. To propose a mode of action of varespladib and CP471474, molecular docking was performed. PLA2s and SVMPs from tested venoms were used as targets. In all cases, our molecular modeling results suggested that inhibitors may occupy the substrate-binding cleft of the enzymes, which was supported by specific interaction with amino acids from the active site, such as His48 for PLA2s and Glu143 for the metalloproteinase. In addition, varespladib and CP471474 also showed interaction with residues from the hydrophobic channel in PLA2s and substrate binding subsites in the SVMP. Our results suggest a synergistic action of the mixed inhibitors and show the potential of varespladib, CP471474, and their mixture to generate new treatments for snakebite envenoming with application in the field or as antivenom co-adjuvants.